2022
DOI: 10.1063/5.0076244
|View full text |Cite
|
Sign up to set email alerts
|

Jet-driven viscous locomotion of confined thermoresponsive microgels

Abstract: We consider the dynamics of micro-sized, asymmetrically coated thermoresponsive hydrogel ribbons (microgels) under periodic heating and cooling in the confined space between two planar surfaces. As the result of the temperature changes, the volume and, thus, the shape of the slender microgel change, which leads to repeated cycles of bending and elastic relaxation, and to net locomotion. Small devices designed for biomimetic locomotion need to exploit flows that are not symmetric in time (non-reciprocal) to esc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…Some recent studies have shown that responsive hydrogels are able to generate substantial bulk fluid motions, such as cyclic swelling of bilayer ribbons causing net swimming (Tanasijević et al. 2022), but in this reported case, this was possible because of some significant asymmetry in the material composition of the particle due to impermeable sections of the boundary, which caused shape change and asymmetric fluid flow across the boundary.…”
Section: Poro-mechanics Of a Swelling Spherical Gelmentioning
confidence: 88%
“…Some recent studies have shown that responsive hydrogels are able to generate substantial bulk fluid motions, such as cyclic swelling of bilayer ribbons causing net swimming (Tanasijević et al. 2022), but in this reported case, this was possible because of some significant asymmetry in the material composition of the particle due to impermeable sections of the boundary, which caused shape change and asymmetric fluid flow across the boundary.…”
Section: Poro-mechanics Of a Swelling Spherical Gelmentioning
confidence: 88%